Hubungan antara Fertilitas, Mortalitas, dan Migrasi dengan Laju Pertumbuhan Penduduk - Ainy, Hidayatul; Nurrochmah, Siti; Katmawanti, Septa (citeus, 2019)
The low rate of population growth in Klojen Districts, cause the population in the region continues to decrease. Reduced population will affect the availability of human resources in the Klojen District. Therefore, conducted a study entitled